Barriers to Entry: Who Decides and Who Benefits? - Anna Maria Tri Anggraini; Sabirin, Ahmad; Raafid Haidar Herfian (Media Iuris, 2026)
Prohibiting the entry of competitors (barriers to entry) into the relevant market is an activity forbidden by Law No. 5 of 1999. Dominant business actors do not solely instigate barriers to entry; regulations can also pose challenges for new entrants to compete in the relevant market. This research aims to identify the factors that create entry barriers imposed by business actors, leading to unhealthy business competition. The research approach uses qualitative-empirical methods, focusing on KPPU decisions, such as Number 15/KPPU-L/2018 and Number 14/KPPU-L/2015. The research findings and analysis reveal that barriers to entry may result from incumbent business actors' actions and/or regulations that facilitate the entry of new players. An example of a barrier to entry, as highlighted in KPPU decisions, involves the issuance of internal office memos that impose restrictions on the sale of competitors' products and impose high tariffs that increase competitors' production costs. A novelty in this study lies in the disclosure of power dynamics in decision-making and profit distribution among stakeholders that affect market accessibility. Then, the authors recommended that the KPPU provide clear guidelines on the term barriers to entry and that business actors develop compliance guidelines to prevent violations of Law No. 5 of 1999.